Modelling of electromechanical drive systems with the use of modal condensation - Gasiorek, Damian; Mežyk, Arkadiusz; Switoński, Eugeniusz (Transport, 2005)
This paper presents a method of developing a dynamic model enabling the study of the effect of the flexibility of the housing on dynamic phenomena in electromechanical drive systems. The research was performed on the basis of an electromechanical model with feedback between the mechanical subsystem (toothed gear with housing) and the electrical subsystem using a software package developed by the author in MATLAB environment.First Published Online: 27 Oct 2010